Size of wild and hatchery-reared Atlantic salmon populations in the northern Baltic Sea estimated by a stratified mark-recapture method - Siira, Antti; Suuronen, Petri; Kreivi, Petri; Erkinaro, Jaakko (ICES Journal of Marine Science, 2006)
11 pages, 5 figures, 4 tables We estimated the total size of the Atlantic salmon (Salmo salar) population complex (wild and cultured) in the Gulf of Bothnia, northern Baltic Sea, using a stratified mark-recapture method. In 2001 and 2002, 1970 salmon were captured by the commercial trapnet fishery and tagged with external arrow tags. A total of 349 tagged fish was later recaptured among 65 180 salmon screened for tags. Recoveries were gathered by the commercial trapnets and by screening fish entering counting facilities in rivers and broodstock fisheries at the river mouths. In addition, tags were recovered from recreational river catches. Our estimates suggest that the total size of the migrating population in both years was about 230 000 fish. Proportions of wild and cultured salmon differed between the two years. In 2001, the proportion of wild salmon was 37%; the corresponding figure for 2002 was 62%. Based on estimates of wild salmon smolt production and the number of released smolts, the estimated proportion of cultured smolts that survived the feeding migration and returned to the Gulf of Bothnia (2-4%) was approximately 2.5-4.5 times lower than that of wild smolts (9-10%). © 2006 International Council for the Exploration of the Sea Peer Reviewed